When will the coughing stop? Characteristics of children with pertussis (whooping cough) in Armenia (2014-2018) - Sose Margaryan; Markus Wells; Hripsime Apresyan; Tatevik Grigoryan; Kristina Akopyan; Olga Denisiuk; Rony Zachariah; Karapet Davtyan (Journal of Infection in Developing Countries)
Introduction: Despite the reported cases of whooping cough in Armenia, there has been no formal evaluation of “who these cases are and their load on hospital wards”. In a tertiary reference hospital, we determined the trend in hospitalized pertussis cases stratified by vaccination status and risk factors associated with apnea and hospital stay.